Analysis of Factors Associated with Acute Myocardial Infarction (AMI) - Siti Nur Hasina; Rahmadaniar Aditya Putri; Riska Rohmawati; Imamatul Faizah; Ratna Yunita Sari (Journal Of Nursing Practice, 2025)
Background: The high mortality and morbidity rates for AMI are caused by delays in treatment efforts, accuracy and speed of diagnosis, and treatment by doctors. There are risk factors that may increase the risk of experiencing an acute myocardial infarction such as age, gender, race, genetics, overweight or obesity, smoking, hyperlipidemia, history of hypertension, diabetes mellitus, stress, and lack of physical activity. Purpose: The purpose of this study was to analyze what factors were associated with the incidence of acute myocardial infarction (AMI) at the Heart Polyclinic at Bhakti Dharma Husada Hospital, Surabaya. Methods: Analytical research design with cross-sectional approach. The population of this study were patients at the cardiac specialist polyclinic with a diagnosis of AMI with as many as 50 respondents. Sampling technique Non-probability sampling and the technique used is Consecutive sampling. Variables in the Independent Variable (Independent Variable) study were age, gender, hypertension, smoking, cholesterol, diabetes, obesity, physical activity. The dependent variable in this study was the incidence of acute myocardial infarction. Results: The results of the study used the Chi Squared tests (α = 0.05) to obtain a ρ-value Age = 0.004, Gender = 0.001, HT = 0.004, Cholesterol = 0.000, Smoking = 0.001, DM = 0.035, BMI = 0.018, Activities = 0.265. This means that there is a relationship between Age, Gender, Cholesterol, Smoking, DM, BMI with the incidence of AMI, and there is no relationship between Activity and the occurrence of AMI. Conclusion: Factors such as age, gender, hypertension, cholesterol, smoking habits, diabetes mellitus, and obesity have been shown to be significantly associated with the incidence of acute myocardial infarction, so that identification and control of these factors are important for the prevention and management of cases in the community. If left for a long time and education is not carried out as early as possible, it will impact the health of the community, which is at risk of more incidents than people who are not exposed to this education.